MEDIA CONSTRUCTION ON INDONESIA POLITICAL CONFLICT: A FRAMING ANALYSIS OF KPK VS POLRI CASE - Yoanita, Desi; Nugroho, Aylanda Dwi; Lesmana, Fanny (PEOPLE: International Journal of Social Sciences, 2015)
The same event can be reported different by different media. That is what we called media framing. As disclosed Gamson et al. (1992), this time we are surrounded by a world of visualization displayed by the media. The visualization of constructing meaning about various things, including political and social issues the message that we receive is not neutral but shows the power and angle of view of political and economic elite behind the news. The system is built with so genius that the whole process seems so normal and natural that most of the audience is not aware if they had been constructed only see reality, not real. Metro TV and TV one are two national televisions which are opposition in 2014 election. Metro TV, which owned by Surya Palo, supported Jokowi-Jusuf Kalla, while TV one, which part of Bakrie Group, supported Prabowo-Hatta. This research aimed to know those two televisions framing of Jokowi in Corruption Eradication Commision (KPK) vs. Indonesia’s Police Force (Polri) matter. Framing model which used to analyze is Gamson-and-Modigliani. There are two tools in this model, which are framing devices that comprise metaphors, catchphrases, exemplaar, depiction, and visual images; and reasoning devices that comprise roots, appeals to principle, and consequences. The research resulted that the framing of those two televisions are different in the matter mentioned above.